PENGEMBANGAN SISTEM INFORMASI PENENTUAN PRESTASI KARYAWAN TELKOM DIVRE IV BERBASIS DSS DENGAN MENGGUNAKAN METODE AHP - Sri Wahyuning, Sindhu Rakasiwi , (ELKOM, 2014)
PT. Telkom Regional Division IV Semarang is a large telecommunications company which has many employees. Information rapid, complete and accurate is needed in the process of determining the performance of employees. However, the use of computers is still relatively less than perfect and adequate in determining achievement so there are no barriers.In this study the parameters that researchers use to analyze problems determination of employee achievement of Telkom Regional Division IV is Strategic Orientation, Organizational Awareness, Learning Ability, Action Management, and Decision Making. Of the five parameters which later can be used to analyze whether the good performance of employees or do not.With the decision support system using AHP method has been petrified solve problems and assist the HR in decision-making to determine employee performance becomes more accurate.Keywords: ahp, dss, employee performance